Intraoperative Localization Of The Marginal Mandibular Nerve In The Pakistani Population: A Cross-Sectional Study - Mishal Rehman; Muhammad Wasim Ibrahim; Maidah Hanif (Journal of Rawalpindi Medical College)
Objective: This study aims to evaluate the proximity of the marginal mandibular nerve to the lower border of the mandible in the Pakistani population, in comparison with previous studies to reduce the risk of inadvertent nerve damage during surgical interventions.